2021
DOI: 10.1016/j.biotri.2021.100192
|View full text |Cite
|
Sign up to set email alerts
|

TiN-Ag as an antimicrobial and wear resistant coating

Abstract: Nosocomial infections are a major clinical concern, posing great risks for patients and rising costs for health services providers. This work aims at developing a hard, wear resistant coating, whose antimicrobial properties shall prevent the transmission of infections.TiN coatings deposited by Physical Vapour Deposition, PVD, with different Ag contents have been studied, especially in relation to the hardness and adhesion, their microstructure and morphology. The antimicrobial activity of the surfaces has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Increasing Ag content also provided a reduction in the coefficient of friction but this was accompanied by reductions in hardness for all the coatings and wear resistance for some of the coatings. More recently (2021), Braceras et al [64], also investigated Ag-TiN as an antimicrobial and wear-resistant coating in the range 4-66 at.% Ag. They showed some excellent results for antimicrobial activity but again this was counteracted by a gradual decrease in hardness with increasing Ag content in the films.…”
Section: Silvermentioning
confidence: 99%
“…Increasing Ag content also provided a reduction in the coefficient of friction but this was accompanied by reductions in hardness for all the coatings and wear resistance for some of the coatings. More recently (2021), Braceras et al [64], also investigated Ag-TiN as an antimicrobial and wear-resistant coating in the range 4-66 at.% Ag. They showed some excellent results for antimicrobial activity but again this was counteracted by a gradual decrease in hardness with increasing Ag content in the films.…”
Section: Silvermentioning
confidence: 99%
“…SEM analyses were performed to assess the surface characteristics and the presence of nanoparticles, possibly of Ag. Different authors [19,30] report that TiN-Ag coatings are composed of Ag clusters segregated at the TiN grain boundaries and are revealed as bright spots in the SEM micrographs. This is confirmed in the present study.…”
Section: Composition Microstructure and Morphology Of Tin-ag Coatingsmentioning
confidence: 99%
“…Studies involving TiN/Ag multilayers deposited on titanium alloys showed the formation of a film with antibacterial properties [19][20][21][22]. In this context, the formation of decorative TiN films with silver becomes interesting and can play an important role in protecting sanitary metals from the formation of biofilms.…”
Section: Introductionmentioning
confidence: 99%